2017
DOI: 10.1210/jc.2017-00825
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol Therapy After Menopause Mitigates Effects of Stress on Cortisol and Working Memory

Abstract: We present evidence suggesting ET may protect certain types of cognition in the presence of stress. Such estrogenic protection against stress hormone exposure may prove beneficial to both cognition and the neural circuitry that maintains and propagates cognitive faculties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 45 publications
1
29
1
1
Order By: Relevance
“…We evaluated the mental health of women healthcare professionals in the UAE using an objective and reliable tool (salivary cortisol levels) to measure stress, as well as subjective psychological measures of stress and sleep quality. [28][29][30] Importantly, we found that a considerable number of women healthcare professionals had an impaired response to stress and demonstrated abnormal cortisol levels, particularly those working night shift and with longer shift duration. Chronic stress has been linked to the onset of mental health problems and overall poorer physical status in working women, [31][32][33] potentially leading to poor physical and social health, and suboptimal performance at work.…”
Section: Discussionmentioning
confidence: 65%
“…We evaluated the mental health of women healthcare professionals in the UAE using an objective and reliable tool (salivary cortisol levels) to measure stress, as well as subjective psychological measures of stress and sleep quality. [28][29][30] Importantly, we found that a considerable number of women healthcare professionals had an impaired response to stress and demonstrated abnormal cortisol levels, particularly those working night shift and with longer shift duration. Chronic stress has been linked to the onset of mental health problems and overall poorer physical status in working women, [31][32][33] potentially leading to poor physical and social health, and suboptimal performance at work.…”
Section: Discussionmentioning
confidence: 65%
“…Moreover, concerning dementia, some papers have found benefits of this treatment to the brain, such as the Cache County prospective study, which analyzed 5,677 women and found a correlation between a lower risk of Alzheimer's disease and this hormonal therapy, especially when medication was taken for more than 10 years [9]. The same was described by Herrera et al [10]. Beneventi et al [11] stressed the importance of keeping in mind the negative long-time effects of female hormone absence, namely regarding vaginal dryness, urinary tract infections and dyspareunia.…”
Section: Introductionmentioning
confidence: 67%
“…This is in accordance with the position statement of the North American Menopause Society [7], which says that the risk of breast cancer is rare while on gonadal steroids. This population has high levels of anxiety and depression and, as such, we cannot miss the serotonergic action that estradiol has on the brain [10], which may provide the patients with better mental health. Some sleep disturbances might ameliorate with progesterone, which has sedating effects without affecting daytime cognitive functions [7].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations